Penerapan Perencanaan Pajak dalam Keputusan Pembelian Mixer Truck Kaitannya dengan Penghematan Pajak (Studi Kasus pada PT. Duta Bangsa Mandiri, Pasuruan) - Antarestia Kartika Putri; Jimmy Andrianus (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This research has a purpose to provide an overview in selecting a more favorable purchasing alternative for truck mixer between cash, credit bank and leasing with option in PT. Duta Bangsa Mandiri Pasuruan to achieve tax savings. This study is a descriptive qualitative research where data is collected and then compiled, interpreted, analyzed, and classified in accordance with the actual events. The analysis techniques are: (1) calculate the fiscal cost; (2) calculate deductible expense; and (3) calculate the tax saving for each alternative. This result of this study shows that leasing with option produces the highest tax saving because deductible expense of alternative leasing with option higher than other alternatives. Based on the conclusion, PT. Duta Bangsa Mandiri is advised to choose an alternative purchase trough leasing with option that brings highest tax saving. Keywords: Tax Planning, Purchasing Alternative, Tax Saving